Positive parenting style and positive health beyond the authoritative: Self, universalism values, and protection against emotional vulnerability from Spanish adolescents and adult children - Palacios, Iria; Garcia, Oscar F.; Alcaide, Marta; Garcia, Fernando (Frontiers in Psychology, 2022)
Recent research is full questioning whether the combination of parenting warmth and strictness (the authoritative style) is always identified as the positive parenting across the globe. This study analyzes parental styles and the positive health of adolescents and adults’ children. The sample was 2090 Spanish children (59.9% female), from four age groups, 600 adolescents, 591 young-adults, 507 middle-aged adults and 392 older-adults. Parenting styles (indulgent, authoritative, authoritarian, and neglectful) were obtained by warmth and strictness measures. Children’s positive health was measured by self (family self-concept, self-esteem, and negative self-efficacy), universalism values and emotional vulnerability. Main results showed that the indulgent parenting style was associated with equal and even better scores than the authoritative style, whereas the authoritarian and neglectful styles were consistently associated with low scores in positive health indicators for all age groups. However, two triple interactions of sex by age group by parenting style showed that women children from neglectful families reported the lowest family self-concept in old age and the highest emotional vulnerability in middle age. Study findings questioning the universally benefits of the so-called positive parenting (the authoritative style) for a positive health.